EFL Secondary Education Teachers' Perceptions Toward Using Online Student Response Systems - Marco Cancino; Paloma Ibarra (Universidad Nacional de Colombia, 2023)
This mixed-methods study explored 30 EFL teachers' perceptions of online student response systems (OSRSs) in emergency remote teaching settings. Data were collected using a survey addressing components related to the acceptance and use of OSRSs and semi-structured interviews. Survey findings revealed that OSRS components are regarded as helpful and engaging by EFL teachers. At the same time, interview data identified drivers (ease of use, increased student engagement, and immediate feedback) and obstacles (internet connection issues, lack of training, and distractive elements) concerning OSRS use. Pedagogical implications refer to the need for EFL teachers to receive proper training before using OSRSs and the benefits of accepting the gamified aspects of OSRSs as a significant feature that can support learning.